An Analysis of Students’ Difficulties in Reading Comprehension of Descriptive Text - Vira Fauziah (Lesson Journal: Languange, Applied Linguistics, and Education Journal, 2021)
An Analysis of Students’ Difficulties in Reading Comprehension of Descriptive Text Vira Fauziah1*, Suparmi2 , Rahma Dania3 Universitas Putra Indonesia “YPTK” Padang2 viraarrahman@gmail.com Abstract This study aimed (1) to find out the difficulties that students found in reading comprehension in descriptive texts, (2) to find out the difficulty factors that affect students in reading comprehension of descriptive texts for the first grade Tata Boga 1 class at SMK N 9 Padang. This research is a qualitative. The techniques of collected the data are questionnaire, interview, observation and document analysis. The subjects of this study were 35 students of first grade Tata Boga 1. The results of the data that have been obtained, there are 69.5% of students find difficulties with very strong answers to the difficulties they find. Then 23.1% of students found difficulties with the usual category. Furthermore, 6.3% of students who did not find it very difficult and finally 1.1% of students who did not find it difficult at all. The factors that influence their difficulty in understanding descriptive text readings are the lack of vocabulary they master, the lack of motivation to learn English as a foreign language, studying without a tutor or studying online, and environmental factors or school associations that are less supportive.